Systematic Literature Review : Peran Guru dalam Pemanfaatan Artificial Intelligence untuk Meningkatkan Kualitas Pembelajaran di Era Digital - Gerasela Gerasela; Ragil Pangestu; Dapid Aryando; Syarifuddin Syarifuddin; Feralia Eka Putri (Yayasan Literasi Sains Indonesia, 2026)
Digital transformation in the education sector has positioned Artificial Intelligence (AI) as a crucial instrument in supporting the learning process. This study aims to systematically analyze the strategic role of teachers in utilizing AI to improve the quality of learning in the digital era. The method used is a Systematic Literature Review (SLR) with the PRISMA 2020 protocol. Based on inclusion and exclusion criteria in reputable journal databases for the 2022–2026 period, 26 final articles were selected for thematic analysis. The results show that the integration of AI technology, such as adaptive learning systems and generative AI, requires a shift in the teacher's role from a material deliverer to a technology orchestrator and instructional designer. AI is proven to improve learning quality through material personalization and assessment efficiency. However, its effectiveness highly depends on the accuracy of platform selection and the teacher's ethical competence. The main challenges identified include the digital infrastructure gap, the need for increased AI literacy for educators, and the integration of ethical values in technology use. This study concludes that AI does not replace the teacher's role, but rather strengthens the teacher's position as an essential educational curator in the modern learning ecosystem.